Mate choice confers direct benefits to females of Anastrepha fraterculus (Diptera: Tephritidae) - Bachmann, Guillermo Enrique; Devescovi, Francisco; Nussenbaum, Ana Laura; Milla, Fabian Horacio; Shelly, Todd E.; Cladera, Jorge Luis; Fernandez, Patricia; Vera, María Teresa; Segura, Diego Fernando (Public Library of Science, 2019)
Exposure to plant compounds and analogues of juvenile hormone (JH) increase male mating success in several species of tephritid fruit flies. Most of these species exhibit a lek mating system, characterized by active female choice. Although the pattern of enhanced male mating success is evident, few studies have investigated what benefits, if any, females gain via choice of exposed males in the lek mating system. In the South American fruit fly, Anastrepha fraterculus, females mate preferentially with males that were exposed to volatiles released by guava fruit or treated with methoprene (a JH analogue). Here, we tested the hypothesis that female choice confers direct fitness benefits in terms of fecundity and fertility. We first carried out mate choice experiments presenting females with males treated and non-treated with guava volatiles or, alternatively, treated and non-treated with methoprene. After we confirmed female preference for treated males, we compared the fecundity and fertility between females mated with treated males and non-treated ones. We found that A. fraterculus females that mated with males exposed to guava volatiles showed higher fecundity than females mated to non-exposed males. On the other hand, females that mated methoprene-treated males showed no evidence of direct benefits. Our findings represent the first evidence of a direct benefit associated to female preference for males that were exposed to host fruit odors in tephritid fruit flies. Differences between the two treatments are discussed in evolutionary and pest management terms.